Relative hyperglycemia is associated with complications following an acute myocardial infarction: a post-hoc analysis of HI-5 data - Tien F. Lee; Morton G. Burt; Leonie K. Heilbronn; Arduino A. Mangoni; Vincent W. Wong; Mark McLean; N. Wah Cheung (Cardiovascular Diabetology, 2017)
Abstract Background Hyperglycemia is associated with increased morbidity and mortality in patients with an acute myocardial infarction (AMI). We evaluated whether complications after AMI are associated with absolute or relative glycemia. Methods A total of 192 patients with AMI were randomized to intensive or conventional insulin therapy. Absolute glycemia was defined as mean blood glucose level (BGL) during the first 24 h following randomization. Relative glycemia was defined by the stress hyperglycaemia ratio (SHR), calculated as mean BGL divided by average glucose concentration over the prior 3 months estimated from glycosylated haemoglobin. The primary endpoint was a “complicated AMI”, defined as an AMI complicated by death, congestive cardiac failure, arrhythmia, cardiac arrest, reinfarction, cardiogenic shock, inotrope use or emergency revascularization. Results There was not a significant association between mean BGL and complicated AMI (odds ratio (OR) 1.05 per mmol/L glucose increment, 95% confidence intervals (CI) 0.93–1.19). In contrast, SHR was positively associated with a complicated myocardial infarction (OR 1.22 per 0.1 SHR increment, 95% CI 1.06–1.42), and individual complications of death (OR 1.55, 95% CI 1.14–2.11), congestive cardiac failure (OR 1.27, 95% CI 1.05–1.54), arrhythmia (OR 1.31, 95% CI 1.12–1.54) and cardiogenic shock (OR 1.42, 95% CI 1.03–1.97). The relationship between SHR and a complicated AMI was independent of diabetic status, intensive insulin therapy, sex and hypoglycemia. Conclusions Relative, but not absolute, glycemia during insulin treatment is independently associated with complications after an AMI. Future studies should investigate whether basing therapeutic glycaemic targets on relative glycemia improves patient outcomes.